2013
DOI: 10.1016/j.cell.2012.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Chromatin State Transitions Associated with Developmental and Environmental Cues

Abstract: Differences in chromatin organization are key to the multiplicity of cell states that arise from a single genetic background, yet the landscapes of in vivo tissues remain largely uncharted. Here we mapped chromatin genome-wide in a large and diverse collection of human tissues and stem cells. The maps yield unprecedented annotations of functional genomic elements and their regulation across developmental stages, lineages, and cellular environments. They also reveal global features of the epigenome, related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

43
486
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 494 publications
(539 citation statements)
references
References 64 publications
43
486
1
3
Order By: Relevance
“…The interplay between environmental cues and epigenetic changes has been described at length in the context of cellular development and/or pathogenesis, yet not much is known about the role of the tissue environment in maintaining the epigenome of normal somatic cells (Feil and Fraga 2011;Zhu et al 2013). This is partly because most human studies have been largely limited either to epidemiological approaches, where exposure time is often unknown, or in vitro systems, which, while useful, do not always recapitulate in vivo conditions (Wilson and Jones 1983;Christensen et al 2009;Cortessis et al 2012;Mill and Heijmans 2013;Zhu et al 2013).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The interplay between environmental cues and epigenetic changes has been described at length in the context of cellular development and/or pathogenesis, yet not much is known about the role of the tissue environment in maintaining the epigenome of normal somatic cells (Feil and Fraga 2011;Zhu et al 2013). This is partly because most human studies have been largely limited either to epidemiological approaches, where exposure time is often unknown, or in vitro systems, which, while useful, do not always recapitulate in vivo conditions (Wilson and Jones 1983;Christensen et al 2009;Cortessis et al 2012;Mill and Heijmans 2013;Zhu et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…This is partly because most human studies have been largely limited either to epidemiological approaches, where exposure time is often unknown, or in vitro systems, which, while useful, do not always recapitulate in vivo conditions (Wilson and Jones 1983;Christensen et al 2009;Cortessis et al 2012;Mill and Heijmans 2013;Zhu et al 2013). Our study using the human ileal neobladder is the first model that attempts to characterize and quantify the dynamic interaction between the local tissue environment and the epigenetics in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the journey from pluripotency to terminal cell types traverses a series of commitments, bivalent promoters resolve to a monovalent active or repressed status (27,28). The NIH Epigenome Roadmap recently determined that large heterochromatin domains are established to restrict committed cells from performing off-target functions (28).…”
Section: Discussionmentioning
confidence: 99%
“…Most GCs are adenocarcinomas, and recent exome-and whole-genome sequencing studies have revealed new GC driver genes and mutational signatures [2][3][4] . Besides protein-coding genes, somatic changes in regulatory elements located in non-coding genomic regions are also likely contributors to malignancy, as these elements can profoundly influence chromatin structure and gene expression [5][6][7] . Regulatory elements can be altered by epigenetic mechanisms including changes in DNA and histone methylation patterns-in many cancers, these have been associated with methylation-induced transcriptional silencing of tumour suppressor genes 8 , chromosomal instability 9 and loss of imprinting 10 .…”
mentioning
confidence: 99%